2023
DOI: 10.1021/acsnano.2c09893
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Ozone-Enriched Spray Gel for Postsurgical Treatment of Hepatocellular Carcinoma

Abstract: Surgical resection of hepatocellular carcinoma suffers from a high recurrence rate. Ozone directly kills tumor cells by generating reactive oxygen species in vitro, but its high reactivity and short half-life severely limit its tumor accumulation and penetration for the treatment of tumors in vivo. Herein, a thermoresponsive ozone-enriched spray gel is developed to suppress the tumor recurrence of hepatocellular carcinoma (Huh-7 tumors). Briefly, a perfluorocarbon nanoemulsion (PFTBA@LIP) consisting of a perfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…2e, the highresolution C 1s spectrum can be divided into six peaks including 284.56, 285.25, 285.87, 286.39, 288.20, and 292.50 eV, corresponding to C-C (sp 2 ), C-C (sp), CvN, C-O, CvO, and π-π* transitions, respectively. 24,39,40 In the N 1s spectrum shown in Fig. 2f, two peaks located at 399.76 eV and 398.78 eV can be attributed to pyrrole N and aza N in the phthalocyanine structure, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2e, the highresolution C 1s spectrum can be divided into six peaks including 284.56, 285.25, 285.87, 286.39, 288.20, and 292.50 eV, corresponding to C-C (sp 2 ), C-C (sp), CvN, C-O, CvO, and π-π* transitions, respectively. 24,39,40 In the N 1s spectrum shown in Fig. 2f, two peaks located at 399.76 eV and 398.78 eV can be attributed to pyrrole N and aza N in the phthalocyanine structure, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 During various coupling reactions, the alkyne-alkyne homocoupling reaction has been applied to synthesize graphdiyne carbon material and its analogs, and the strategy has been demonstrated to be an efficient method to construct diyne linked (-CuC-CuC-) POPs. 23,24 Due to their unique 18π electronic and designable structures, phthalocyanines have been considered to be perfect building blocks for conjugated porous materials 25,26 and have great application potential in the fields of catalysis, 27,28 energy storage, 29,30 and electronic devices. 31,32 In the phthalocyanine skeleton, the pyrrolic nitrogen atoms and aza nitrogen atoms have stronger electronegativity than carbon, 33,34 meanwhile, the sp-hybridized carbons have stronger electronegativity than sp 2 carbons, 35,36 resulting in good affinity and interactivity with Li + , which is probably beneficial for the improvement of lithium storage ability.…”
Section: Introductionmentioning
confidence: 99%
“…And in the second step due to electrostatic interactions, opposite free ions in the liquid are attracted to the charged FEP surface. 21,41 Aer the droplet separated from the FEP surface, the adsorbed ions le on the FEP surface will shield the transferred charges measured. In this way, the longer the contact time between the droplet and FEP, the more ions have chance to adsorb on the FEP, and thus the stronger shielding effect should be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, acyl-CoA synthetase long-chain family member 4 (ACSL4) acts as a component of the essential enzyme ferroptosis execution . The upregulation of ACSL4 can contribute to the accumulation of lipid intermediates during cell ferroptosis. , As shown in Figure e, immunofluorescence analysis indicated that the expression levels of ACSL4 showed a clear increasing trend after MCF-7 cells were treated with CuS@hMnO 2 , CQ/PEG-CuS@hMnO 2 , and CQ/PEG-CuS@hMnO 2 +NIR.…”
mentioning
confidence: 95%